Analysis of factors affecting the use of implantable contraceptives in couples of fertile age: A cross-sectional study - Hilaliah; Ali Harokan; Erna Gustina; Dewi Suryanti (Lentera Perawat, 2025)
Background The use of contraceptive implants as a long-acting contraceptive method remains low in Indonesia, including in the working area of the Muara Enim District Extension Center. Despite its high effectiveness in preventing pregnancy, several factors may influence implant adoption among women of reproductive age, such as age, knowledge, attitude, socioeconomic status, parity, and husband’s support. Objective This study aimed to identify the factors associated with the use of contraceptive implants among reproductive-age couples in the Muara Enim District Extension Center in 2025. Methods This study applied a quantitative cross-sectional design involving 93 respondents selected through purposive sampling. Inclusion criteria were women of reproductive age residing in the study area and willing to participate, while exclusion criteria included serious illness and illiteracy. Data collection was conducted from May 2 to 17, 2025, using a validated structured questionnaire supported by medical record checks. Variables measured included age, knowledge, attitude, socioeconomic status, parity, and husband’s support, with implant use as the dependent variable. Data analysis was performed in three stages: univariate to describe frequencies, bivariate using Chi-square tests to assess associations (p < 0.05), and multivariate using logistic regression to determine dominant factors. Ethical clearance was obtained, and informed consent, anonymity, and confidentiality were ensured.. Results ge (p=0.02), attitude (p=0.005), and socioeconomic status (p=0.02) were significantly associated with implant use, while knowledge (p=1.00), parity (p=0.90), and husband’s support (p=0.18) were not. Logistic regression confirmed attitude as the most dominant predictor (p=0.003; OR=0.26). Conclusion Age, attitude, and socioeconomic status significantly influence implant use, with attitude being the strongest determinant. Health promotion should focus on shaping positive attitudes through couple-based counseling and interpersonal education, especially for younger women and low-income groups.